Approaches to enhancing communication between healthcare providers and recipients. (2017) - Ozgen, Muhsine Itir; Thatchenkery, Tojo
In an effort to improve communication between doctors and patients, doctors in one of the largest research and training hospitals in Istanbul, Turkey were invited to participate in a customised communication training programme and its effectiveness was assessed using surveys. A group of pharmaceutical executives and doctors were interviewed a year later to explore if the doctor-patient communication had indeed improved. Results indicated that the training program had a positive impact on providing doctors with tools and perspectives in interacting with patients with more empathy and understanding. At the same time, external factors such as over-crowding and misuse of the precious research facilities at the hospital for routine healthcare needs of the patients from far off areas came in the way of providing true patient care to those with serious medical needs. More education and communication is needed for encouraging patients to utilise local hospitals for routine needs.